From Tables to Graphs with ClinicoAtlas: Leveraging LLMs to Support Modeling and Mining Knowledge Graphs - Conrado, Rafael C. G.; Campos, Eduardo M.; Traina Jr., Caetano; Traina, Agma J. M.; Cazzolato, Mirela T. (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD); 2025: Anais Estendidos do XL Simpósio Brasileiro de Bancos de Dados, 2025)
Given a set of Electronic Health Records organized as tabular data, how can we model and evaluate relationships between various concepts related to health conditions and treatments? Representing EHRs as Graphs allows a much more intuitive interpretation of relationships between concepts and permits the mining of node features, generating relevant metrics for hospital data analysis. However, these metrics are often generic and difficult to interpret. In this context, Large Language Models can assist in constructing these graphs by defining the semantic relationships between concept pairs and attributing contextual meaning to the extracted features. The proposed ClinicoAtlas tool integrates LLMs into the construction of knowledge graphs, facilitating the extraction and interpretation of meaningful information for healthcare management.